COMPARISON OF INTENSIVE AND EXTENSIVE SYSTEM OF MANAGEMENT IN FEEDLOTTING OF INDIGENOUS BULLS - Sulaiman, I.; Mai, H. M.; Macha, Y. P.; Magaji, I. M.; Adamu, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study compared intensive and extensive systems of management in feedlotting of indigenous bulls at Dairy Research and Development Centre ATBU, Bauchi. Haematological examination, serum biochemical and parasitological tests of blood samples were analysed. All measurements were taken early in the morning prior to feeding. There was significant difference (P<0.05) in haematological values, with intensive system having the superior mean corpuscular haemoglobin (MCH=23.93±0.64), mean corpuscular haemoglobin concentration (MCHC=39.65±0.74), Platelet (PLT=294.17±27.26) and neutrophils (NEUT=46.62±4.13) while Red blood cell (RBC=5.74±0.36), haemoglobin (HB=11.23±0.47) were lower in intensive but higher among animals raised under extensive system. Glucose concentration (GC=3.77±0.11) was significantly higher (P<0.05) among intensively raised bulls. Extensive system showed significantly higher (P<0.05) prevalence of blood and faecal parasites except for Cooperia pectinata which was higher in intensive system. Bulls raised under extensive system (42.36%) showed higher return on investment than bulls raised under intensive system. Bulls managed under intensive feedlot demonstrated higher significant values of MCH, MCHC, PLT, NEUT & GC except RBC & Hb which were high in extensive system. Extensive system showed significantly higher parameters of blood and faecal parasites except for Cooperia pectinata which was higher in intensive system. Parasite can cause low haematological values leading to poor physiological status of animals hence, low productivity. It is recommended that in the absence of facilities and other resources for intensive feedlotting, farmers should adopt partial extensive system and, parasitic control should be paramount to whatever system adopted.